Molecular evolution and regulation of DHN melanin-related gene clusters are closely related to adaptation of different melanin-producing fungi - Jia, Shu-Lei; Chi, Zhe; Chen, Lu; Liu, Guang-Lei; Hu, Zhong; Chi, Zhen-Ming (Genomics (San Diego, Calif.), 2021)
Many genes responsible for melanin biosynthesis in fungi were physically linked together. The PKS gene clusters in most of the melanin-producing fungi were regulated by the Cmr1. It was found that a close rearrangement of the PKS gene clusters had evolved in most of the melanin-producing fungi and various functions of melanin in them were beneficial to their adaptation to the changing environments. The melanin-producing fungi had undergone at least five large-scale differentiations, making their PKS gene clusters be quickly evolved and the fungi be adapted to different harsh environments. The recent gene losses and expansion were remarkably frequent in the PKS gene clusters, leading to their rapid evolution and adaptation of their hosts to different environments. The PKS gene and the CMR1 gene in them were subject to a strong co-evolution, but the horizontal gene transfer events might have occurred in the genome-duplicated species, Aspergillus and Penicillium. •Many melanin-synthesizing genes are linked together as the PKS gene clusters.•Most of the PKS gene clusters are regulated by Cmr1.•Evolution of different genes in the clusters is closely related to adaptation of the melanin-producing fungi.